Prognostic value of serum free light chain abnormalities in diffuse large B-cell lymphoma - Jia, Zhuxia; Li, Jin; Liu, Jie; Han, Wenmin; Xu, Wei; Lu, Xuzhang (Frontiers in Oncology, 2025)
IntroductionThis study aimed to evaluate the prognostic significance of serum free light chain (FLC) abnormalities in patients diagnosed with diffuse large B-cell lymphoma (DLBCL), with an emphasis on associations with clinical characteristics and survival outcomes.MethodsThis retrospective study included 259 patients newly diagnosed with DLBCL. Serum FLC levels in patients diagnosed with DLBCL were measured prior to the initiation of chemotherapy.ResultsComparing to normal FLC, abnormal serum FLC levels were significantly associated with several clinical features including age > 60 years (p = 0.01), advanced diseased stage (stage III/IV, p < 0.001), involvement of multiple extra nodal sites (p = 0.019), elevated lactate dehydrogenase (LDH) (p = 0.005), Eastern Cooperative Oncology Group performance status (ECOG PS) scores of >1 (p = 0.02), high-intermediate to high International Prognostic Index (IPI) scores (p = 0.005), bone marrow infiltration (p = 0.001), presence of B symptoms, and a higher prevalence of non-germinal center B-cell (non-GCB) subtype. While monoclonal FLC expression was associated with advanced disease stages (stage III/IV, p < 0.001), high-intermediate to high IPI scores (p < 0.001), bone marrow infiltration (p < 0.001), elevated LDH (p < 0.001), and categorization within high-risk prognostic groups. Distinct clinical characteristics were also observed between patients with normal and abnormal serum FLC levels based on molecular classification. Among 259 patients, patients with abnormal or monoclonal FLC profiles had significantly reduced three-year overall survival (OS) and progression-free survival (PFS) (p = 0.016 and 0.032 and p = 0.008 and 0.024, respectively) compared to normal FLC profiles. Among patients with non-GCB DLBCL, monoclonal FLC was associated with a significantly reduced three-year OS compared to normal FLC levels (p = 0.008). Results of multivariate Cox regression analysis for FLC as an independent prognostic factor were not statistically significant.ConclusionsAbnormal serum FLC levels were associated with adverse clinical features and inferior survival outcomes in DLBCL, particularly monoclonal FLC in the non-GCB subtype. These findings support the utility of serum FLC assessment as a simple, accessible biomarker for risk stratification in DLBCL, though it was not confirmed as an independent risk factor in multivariate analysis.